Extending Students' Understanding to Learn English Prepositions through Circle Game - Rahmat Rivaldy Laisouw; Nurlaily Sofyan; Adi F. Mahmud (EDU Journal - English Department of UMMU Journal, 2022)
This study aims to extend students' understanding of learning prepositions by using the Circle Game. This study used a quantitative approach with a pre-experimental design one group pretest and posttest. The study was conducted at SMA 2 Negeri Halmahera Utara involving 15 students in the second grade as a sample. The sample is chosen by using a simple random sampling technique. The procedure of data collection are; pretest, treatment, and posttest by using test items as an instrument of the study. The pretest was carried out before learning by using questions that had been prepared by the researchers. After the pretest, it did a learning process (treatment) with the Circle Game. Then a posttest was carried out after the treatment was carried out for four meetings. All data collection was analyzed using the dependent T-test to compare the results of the pretest and post-test with a significant level of 5%. The results of the study showed (1) students' understanding of English prepositional material before treatment with the Circle Game was very low, (2) Circle Game made a very significant contribution to students' understanding of English prepositional material, (3) The null hypothesis stated that Circle Game did not have an impact on increasing students' understanding of the English prepositional material was rejected and the alternative hypothesis was accepted, and (4) the Circle Game not only contributed to increase students’ understanding, but it also had a positive impact on student's motivation and enthusiasm in participating in learning class.